2021
DOI: 10.3390/diagnostics11091701
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Thermography as a Diagnostic Tool for the Assessment of Patients with Symptomatic Peripheral Arterial Disease Undergoing Infrafemoral Endovascular Revascularisations

Abstract: Aim: The aim of this study was to evaluate the utility and reliability of temperature foot changes measured by infrared thermography (IRT) for the evaluation of patients with atherosclerotic peripheral arterial disease (PAD) before and after endovascular revascularisation. Methods: This is an observational prospective study carried out on symptomatic PAD patients. Evaluations consisted of a clinical examination, duplex scan with ankle–brachial index calculation (ABI) and IRT measurements with infrared camera F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…The included studies reported different measurement sites, focusing in particular on the feet. One study did not precisely describe the measurement location [ 45 ], 2 articles studied the ankle and the anterior tibial face [ 39 , 44 ], six the toes [ 2 , 32 , 33 , 41 , 42 , 43 , 48 ], seven the dorsum of the foot [ 31 , 32 , 37 , 38 , 39 , 46 , 49 ] and eleven authors identified the plantar side of the foot, making it the most studied area [ 22 , 32 , 33 , 34 , 35 , 36 , 40 , 42 , 44 , 50 ]. A summary of the measurement locations is reported in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The included studies reported different measurement sites, focusing in particular on the feet. One study did not precisely describe the measurement location [ 45 ], 2 articles studied the ankle and the anterior tibial face [ 39 , 44 ], six the toes [ 2 , 32 , 33 , 41 , 42 , 43 , 48 ], seven the dorsum of the foot [ 31 , 32 , 37 , 38 , 39 , 46 , 49 ] and eleven authors identified the plantar side of the foot, making it the most studied area [ 22 , 32 , 33 , 34 , 35 , 36 , 40 , 42 , 44 , 50 ]. A summary of the measurement locations is reported in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies have monitored the effect of revascularization procedures using IRT [ 33 , 34 , 35 , 39 , 49 ]. Zenunaj et al [ 39 ] evaluated the effectiveness of an intervention by measuring the temperature in both feet before and 24 h after the surgery, observing an improvement of +2.1 °C and +0.5 °C in the limb that underwent the revascularization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations